and Antioxidant Activity of Endophytic Fungi from Mahogoni Plant (Swietenia macrophylla King - Edward J Dompeipen; Partomuan Simanjuntak (Biopropal Industri, 2015)
Diabetes mellitus is a degenerative disease characterized by hyperglycemia due to insulin insulin deficiency either absoluteor relative. This study was conducted to isolate endophytic fungi from plant twigs mahogany (Swietenia macrophylla King) which active as antidiabetic and antioxidant. Antidiabetic activity conducted by using the α-glucosidase inhibitory and antioxidant activity using free radical reduction method with reagent 2.2-diphenyl-1-picrylhydrazyl (DPPH). Isolation of microbes conducted in the media Corn Meal Malt Agar (CMMA) and Potato Dextrose Agar (PDA) which 7 isolates of fungus in total. Inhibitory activity against α-glucosidase to extract the filtrate and biomass of the isolates A.Sm.2F (72.59 and 92.22%), A.Sm.3F (81.87 and 79.37%), B.Sm.1F (63.40 and 98.84%), B.Sm.2F (65.60 and 62.72%), B.Sm.3F (93.91 and 51.48%), B.Sm.4F (87.48 and 74.64%) thus has potential as an antidiabetic activity. B.Sm.1F was the only isolates active as antioxidants with IC50 of 84.41.